(untitled) (Libellarium: časopis za istraživanja u području informacijskih i srodnih znanosti, 2017)
The comparison of the 28 lunar mansions of Daba and Dongba scripts revealed that Daba glyphs are single graphemes that are generally pictograms depicting the star atlases or related to the syllables of the stars names. Their counterparts in Dongba writing, conversely, are mostly ligatures consisting of several graphemes. They could be pictograms depicting the star atlases or the syllabic representations of the lunar mansions designations, or the combinations of both. Basing the analysis on the functions of the glyphs in writing down languages, the plausible path of development that can be highlighted from these two scripts have been reconstructed. Further on, the hypothesis is proposed according to which Daba script could be the initial stage of the Dongba writing system.